Surgical outcome of single site phacotrabeculectomy in management of concurrent glaucoma and cataract - Ramnani, Vinita; Agarwal, Rahul; Singh, Priti; Kumar, Rashmi; Raghuvanshi, Sapna; Ramnani, Vijay Kumar (International Journal of Research in Medical Sciences, 2017)
Background:The aim of our study is to evaluate the efficacy and safety of combined procedure of single site phacoemulsification and trabeculectomy in terms of improvement of visual acuity and intraocular pressure control. Methods: Prospective, noncomparative, consecutive, interventional study of 74 eyes (64 patients) of single site phacotrabeculectomy in cases of primary open angle glaucoma with significant operable cataract from April 2014 to March 2015. Out of 64 patients 30 were male and 34 were female with age ranged 48 to 80 (mean 64.5) years. Ten patient required bilateral surgery. The controlled mean preoperative IOP was 20 mmHg ranged (12- 36 mmHg).Postoperative best corrected visual acuity, intraocular pressure and fundus examination were done one day, one week, one month, three months and one year following surgery. Perimetery was done at third and twelve months. Results: Mean postoperative intraocular pressure after 12 months of follow up was 12 mmHg (range 08 to 20 mmHg) and overall improvement in visual acuity achieved in 90.54% (67) of eyes. Visual acuity of 6/12 and better was achieved in 62.16% (46) eyes. IOP was controlled without any treatment in 83.78% (62) eyes, and rest 16.22% (12) eyes needed antiglaucoma drugs to control IOP. Hyphema and uveitis were common complications noted. Conclusions: Combined phacotrabeculectomy is safe and effective method in restoring vision and lowering intraocular pressure. It helps in early visual rehabilitation and convenient, economical method to manage concurrent glaucoma and cataract.